Hi I have been trying to figure out how this method works.
Searched the forum but got no results. Have attached an example Im trying to do. If someone could show me it would be great.
Or even show me a similar example worked out.
Thanks in advance!
Edit: I am trying another question
u_tt = u_xx
u( x, 0) = 0 = f(x) ?
u_t( x,0) = xe^-(x^2) = g(x)?
So as f(x) = 0 can I just figure out the ingegral of g(x) with limits (x+ct) and (x-tc)
The answer is supposed to be 11 but I just get
1/4 [ -e^(x+t)^2 + e^-(x-t)^2]
I use the formula and as f(x) = 0